A new l-arabinose isomerase with copper ion tolerance is suitable for creating protein–inorganic hybrid nanoflowers with enhanced enzyme activity and stability. Issue 37 (24th March 2016) - Xu, Zheng; Wang, Rui; Liu, Chao; Chi, Bo; Gao, Jian; Chen, Beining; Xu, Hong
Abstract : Protein–inorganic hybrid nanoflowers were prepared using Cu 2+, PBS buffer, and a copper ion tolerantl -arabinose isomerase that was derived from Paenibacillus polymyxa (PPAI). Abstract : Protein–inorganic hybrid nanoflowers were prepared using Cu 2+, PBS buffer, and a copper ion tolerantl -arabinose isomerase that was derived from Paenibacillus polymyxa (PPAI). The expensive rare sugarl -ribulose ord -tagatose was prepared utilizing these nanoflowers withl -arabinose ord -galactose as the substrate, respectively. The PPAI hybrid nanoflowers showed better enzyme stabilities in both thermal and acidic conditions. Meanwhile, long term batch production was successful showing high stability using these hybrid nanoflowers, which achieved a conversion rate of 61.8% froml -arabinose tol -ribulose.